The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1111/j.1476-5381.1988.tb11547.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enalapril on changes in cardiac output and organ vascular resistances induced by α1‐ and α2‐adrenoceptor agonists in pithed normotensive rats

Abstract: 1 Cardiac output, its distribution and regional vascular resistances were determined with tracer microspheres in pithed rats in the presence of the angiotensin converting enzyme inhibitor enalapril.The effects of enalapril on the cardiovascular responses elicited by either the ax-adrenoceptor agonist phenylephrine or the a2-adrenoceptor agonist xylazine were determined. 2 Enalapril decreased diastolic and mean blood pressure by decreasing cardiac index and total peripheral resistance. It induced vasodilatation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The reasons for the discrepant results between their study and ours are not obvious, but factors such as different experimental conditions cannot be excluded. However, enalapril, another ACE inhibitor, was also shown to decrease both CO and TPR in the pithed rat, 11 as we have demonstrated with captopril. Nonetheless, taken together, these data indicate the involvement of endogenous Ang II in maintaining CO in the pithed rat.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The reasons for the discrepant results between their study and ours are not obvious, but factors such as different experimental conditions cannot be excluded. However, enalapril, another ACE inhibitor, was also shown to decrease both CO and TPR in the pithed rat, 11 as we have demonstrated with captopril. Nonetheless, taken together, these data indicate the involvement of endogenous Ang II in maintaining CO in the pithed rat.…”
Section: Discussionsupporting
confidence: 70%
“…Unlike vasopressin, Ang II infusion restored MBP by increasing TPR without altering CO 10 or by increasing CO and TPR. 11 still debatable. On the other hand, our data suggest that nonspecific functional antagonism may not totally explain the inhibitory effect of captopril on the hemodynamic response to sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After haemorrhage, circulating angiotensin II is increased and we have demonstrated previously that, in pithed rats, endogenous angiotensin II facilitates pressor responses to both phenylephrine and xylazine (MacLean & Hiley, 1988b). Angiotensin II may therefore contribute to the facilitatory effect of haemorrhage on the pressor responses to infusions of amidephrine.…”
Section: Discussionmentioning
confidence: 86%
“…The present studies were formulated to ascertain whether previously reported effects of a2 adrenoceptor stimulation on glomerular dynamics involve an interaction with All. The basis for this hypothesis derives in part from similarities between the recently reported glomerular hemodynamic response to B-HT 933 (2) and the well-known response to All (3), as well as from past reports that angiotensin-converting enzyme inhibitors will block a2-mediated vasoconstriction (34)(35)(36). Studies were performed after renal denervation to isolate the effects of stimulating renal a2 receptors from the sympathoinhibitory actions of systemic a2 agonist administration.…”
Section: Discussionmentioning
confidence: 99%